Is Hizb ut-Tahrir Indonesia Part of Islamic Revival? - Santoso, Budi; Sjuchro, Dian Wardiana (Universitas Muhammadiyah Yogyakarta, 2019)
This paper is an attempt to academically define Hizb ut Tahrir Indonesia's characteristics before its revocation. Although the Indonesian regime has officially disbanded this transnational organization in July 2017, its existence remains stimulating to discuss. Hizb ut-Tahrir Indonesia's primary objective is to implement Islamic laws in total, which can only be accomplished within a superstate called al-Khilafah al-Islamiyah (Islamic Caliphate) led by a Khalifah (Caliph). Its followers believe that Islam will revive under the caliphate. In Indonesia, Hizb ut-Tahrir actively criticized the government's policies through its articles, preachings, and street rallies. The ideas were conveyed not only through direct campaigning but also via its internal media. We argue, based on this study, that HTI is part of Islamic revival that wants to change the social-political structures through the re-creation of the caliphate by conducting intensive da'wa with nonviolent activities, as well as war of ideas as the strategy.